Serum extracellular vesicle depletion processes affect release and infectivity of HIV-1 in culture - Zhaohao Liao (Nature Portfolio, 2017)
Abstract Extracellular vesicles (EVs) are involved in intercellular communication and affect processes including immune and antiviral responses. Blood serum, a common cell culture medium component, is replete with EVs and must be depleted prior to EV-related experiments. The extent to which depletion processes deplete non-EV particles is incompletely understood, but depleted serum is associated with reduced viability and growth in cell culture. Here, we examined whether serum depleted by two methods affected HIV-1 replication. In cell lines, including HIV-1 latency models, increased HIV-1 production was observed, along with changes in cell behavior and viability. Add-back of ultracentrifuge pellets (enriched in EVs but possibly other particles) rescued baseline HIV-1 production. Primary cells were less sensitive to serum depletion processes. Virus produced under processed serum conditions was more infectious. Finally, changes in cellular metabolism, surface markers, and gene expression, but not miRNA profiles, were associated with depleted serum culture. In conclusion, depleted serum conditions have a substantial effect on HIV-1 production and infectivity. Dependence of cell cultures on “whole serum” must be examined carefully along with other experimental variables, keeping in mind that the effects of EVs may be accompanied by or confused with those of closely associated or physically similar particles.